The sociology of Islam knowledge, power and civility - Salvatore, Armando (Wiley, 2016)
"The Sociology of Islam is an interpretive account of Islam as a religion and civilization in world history and global society, which focuses on the notions of knowledge-culture, power and civility to provide key interpretive and analytic tools to practitioners. The first substantial introduction to the field of the Sociology of Islam that combines theoretical reflections with historical analysis Explores the original civilizational trajectory of Islam and its specific entry point into modernity Develops a narrative and analytic thread that makes the 'dual' role of Islam - as a religion and civilization - comprehensible to non-specialistsÈ Allows Islamic Studies specialists and students to locate the study of Islam in a comparative perspective with the help of simple, yet rigorous conceptual tools drawn from sociology and social theory The author is a scholar of both the Sociology of Islam and Comparative Civilizational Analysis and ideally placed to write this text"--